Age-related differences in muscle co-activation during locomotion and their relationship with gait speed: a pilot study. Issue 1 (December 2017) - Lee, Hwang-Jae; Chang, Won; Choi, Byung-Ok; Ryu, Gyu-Ha; Kim, Yun-Hee
Abstract Background Muscle co-activation plays an important role in enhancing joint stability for movement regulation during motor learning activities. In normal aging, greater muscle co-activation is induced during gait in elderly adults. This study investigated age-related changes in muscle co-activation and spatio-temporal parameters during gait and identified the relationship between muscle co-activation and gait speed. Methods A total of 46 adult volunteers participated in this study in three age groups (15 young adults [8 males, 7 females; age, 24.27 ± 2.71], 15 middle-aged adults [8 males, 7 females; age, 53.71 ± 2.52], and 16 elderly adults [7 males, 9 females; age, 76.88 ± 3.48]). All participants underwent locomotion analysis using a Three-dimensional motion analysis system and 12-channel dynamic electromyography. Results The elderly adults showed significantly higher co-activation than the young and middle-aged adults during gait (p < 0.05). In contrast, elderly adults showed significantly lower trunk co-activation than the young and middle-aged adults (p < 0.05). Muscle co-activation was significantly correlated with gait speed by aging. Muscle co-activation of the trunk showed a significant positive correlation with gait speed based on age. However, muscle co-activation of the lower extremity showed a significant negative correlation with gait speed based on age. Conclusion This finding demonstrated that less muscle co-activation of the trunk was related to locomotive instability in elderly adults. Therefore, clarification of the relationship between trunk co-activation and locomotor instability will be helpful for developing optimal rehabilitation of elderly people to prevent fall.